Molecular analysis of rpoB, katG and embB gene mutation in mycobacterium tuberculosis isolates from Terengganu, Malaysia - Rashid, Zulkhairi Abdul (2020)
Molecular Analysis of rpoB, katG and embB gene mutation in Mycobacterium tuberculosis isolates from Terengganu Malaysia. The incidence of TB in Malaysia is increasing, and our country is reaching the status of TB high burden countries. Besides the number of TB infection, drug resistance is an emerging too. Molecular characteristics of drug resistance are still limited in the country. In an attempt to understand the distribution of drug-resistance TB, types and frequency of mutation in Terengganu, we analysed rpoB, katG and embB genes for rifampicin, isoniazid, ethambutol, respectively. Mycobacterium tuberculosis isolates collected from microbiology laboratory HSNZ for six months, drug susceptibility result traces from MKA Kota Bharu, and drug-resistant isolates and some drug-susceptible isolates proceed for PCR amplification and DNA sequencing. Genotypic analysis performed to detect the mutations in the sequence of the target genes. 92 Mycobacterium tuberculosis complex isolates collected. 84 (91.3%) drug susceptibility results were available. 13 (15.5%) isolates have drug resistance to at least one drug. Of 13 isolates, only one has rifampicin resistance, three isoniazid resistance and one ethambutol resistant. Isolate with rifampicin-resistant showed a mutation in rpoB S513T. 1 of 3 isoniazid-resistant has a mutation in S315T katG, while the other 2 has no mutation at katG gene. The ethambutol resistant isolate has no embB gene mutation. The other isolate has no mutation in tested genes. Current drug resistance TB cases in Terengganu are low. Molecular characterization of drug resistance shows a common mutation, as reported in various regions of the world. A more extensive study is needed to show more representative data for the country.